Use of STEM-technologies in the educational process in the training of technical profile specialists - Movmyga, N. E.; Polezhaieva, O. V.; Gyrenko, I. V. (Громадська наукова організація "Всеукраїнська асамблея докторів наук з державного управління", 2023)
This article examines the relevance and necessity of introducing an innovative approach to modern education which is called the STEM-approach and is focused on the formation of students' skills in scientific research, engineering, invention, entrepreneurship, and professional self-determination. Today, higher education should provide training of specialists with professional skills that reflect their professional competence, social orientation, values and ability to satisfy personal and social needs, i.e. persons with such a professional level that would meet modern international requirements and standards. The authors analyzed the essential characteristics of the STEM approach as a new and innovative mechanism of transformation of modern higher education through science. The necessity to introduce STEM technologies into the educational process of technical specialists was determined. The advantages of their absorption were identified and the stages of professional education of technical specialists with the help of STEM technologies were determined. The article outlines the need for this application in the perspective of the considered problem. It is determined that STEM education with the help of practice-oriented methods opens up the ways of development and application of scientific and technical knowledge for professional growth to specialists in technical sphere. It provides many opportunities and development of mental, cognitive and creative qualities of future specialists, the level of which determines their competitiveness in the modern labor market: an ability and readiness to solve complex tasks (problems), critical thinking, creativity, cognitive flexibility, cooperation, management, implementation of innovative activities, ability to act effectively in conditions of uncertainty, etc. STEM, as a process of external influence on an individual, is aimed at personal (acquiring authentic practical experience of innovative activity, knowledge management, learning, ecological thinking, emotional intelligence, introspection and reflection) and social (communication, mentoring and monitoring, teamwork, nonviolent communication) aspects. In this regard, the authors also paid attention to the formation of soft skills - developed personal qualities that help to perform work effectively and successfully, build future career and be in demand and stay ompetitive in the modern labor market. Through the conducted research, the authors of the article emphasized that the introduction of STEM technologies into the educational process of technical specialists is aimed at training specialists with a new type of thinking, without which the development of innovative economy and formation of scientific and technical elite of Ukraine are not possible.

В даній статті розглядається актуальність та необхідність впровадження інноваційного підходу в сучасній освіті - STEM-підходу, орієнтованого на формування у здобувачів освіти навичок науково-дослідницької й інженерної діяльності, винахідництва, підприємництва, професійної самовизначеності. На сьогодні вища освіта повинна забезпечувати підготовку фахівців із сформованими якостями, які відображають їх ціннісну орієнтацію, професійну компетентність, соціальну спрямованість і можливість задовольняти особисті й суспільні потреби, осіб із професійним рівнем, який відповідав би сучасним міжнародним вимогам та стандартам. Авторами проаналізовано суттєві характеристики STEM-підходу як нового та інноваційного механізму трансформації сучасної вищої освіти через науку; визначено необхідність впровадження STEM-технологій в освітній процес фахівців технічного профілю, виявлено переваги їх засосування, визначено етапи професійної освіти фахівців технічного профілю за допомогою STEM-технологій. В статті окреслено необхідність цього застосування в ракурсі розглянутої проблеми, та визначено, що STEM-освіта за допомогою практико-орієнтованих методик відкриває фахівцям технічного профілю шляхи розвинення та застосування науково-технічних знань у професійному зростанні, надає безліч можливостей та розвитку розумово-пізнавальних і творчих якостей майбутнього фахівця, рівень яких визначає конкурентну спроможність на сучасному ринку праці: здатність і готовність до розв’язання комплексних задач (проблем), критичного мислення, творчості, когнітивної гнучкості, співпраці, управління, здійснення інноваційної діяльності, здатності ефективно діяти в умовах невизначеності та ін. STEM, як процес зовнішнього впливу на індивіда, також має на меті особистісний (здобуття автентичного практичного досвіду інноваційної діяльності, управління знаннями, навченість, екологічність мислення, емоційний інтелект, самоаналіз та рефлексія) та соціальний (комунікація, наставництво та моніторинг, робота в команді, ненасильницьке спілкування) аспекти. З цього приводу, авторами також приділено увагу формуванню Soft skills - розвиненим особистісним якостям, які допомагають результативно виконувати роботу та успішно будувати майбутню кар’єру, та бути затребуваними та конкурентоспроможними на сучасному ринку праці. Проведеним дослідженням, автори статті підкреслюють, що впровадження STEM-технологій в освітній процес фахівців технічного профілю, спрямоване на підготовку фахівців з новим типом мислення, без яких неможливий розвиток інноваційної економіки та формування науково-технічної еліти України.
Використання STEM-технологій в освітньому процесі при підготовці фахівців технічного профілю
Keywords: STEM-approach; STEM-technologies; hard skills; soft skills; technical sphere specialists; personal and social aspects; professional competence; competitiveness; інформаційні технології; навчальний процес; конкурентоспроможність; професійна компетентність; вища освіта